1989
DOI: 10.1017/s0025315400032148
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the Nervous System of Barnacles: the Median Ocellus ofBalanus Hameri (=Chirona Hameri)(Crustacea: Cirripedia)

Abstract: The barnacle cypris larva possesses a pair of laterally placed compound eyes and a median nauplius eye which is tripartite in structure. Concomitant with the metamorphosis to the juvenile is the loss of compound eyes and the nauplius eye separates into its three constituent parts (Walley, 1969). The two dorsolateral components of the nauplius eye come to lie under the rostral shell plates, whereas the ventral component forms the median ocellus which underlies the mantle flaps of the scutal plates at the poster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The nauplius eye of barnacles is composed of three components (3,12). Kauri (12) has noted that the nauplius eye of The conclusions of the present study are summarized schematically in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nauplius eye of barnacles is composed of three components (3,12). Kauri (12) has noted that the nauplius eye of The conclusions of the present study are summarized schematically in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The view is generally held, although in the absence of detailed investigations of the metamorphosing larvae, that the adult photoreceptors are derived from components of the nauplius eye (5, 6, 9, 21). However, it has been pointed out that there are considerable differences in the number, size and organization of visual cells between the adult and larval photoreceptors (3,7,(11)(12)(13)(14). Further, Bernard and Lane (1) suggested that the larval ocellus did not develop directly into the adult photoreceptors.…”
Section: Introductionmentioning
confidence: 99%
“…The photoreceptors are subdivided by these pigment cells into three groups that "look" in three different directions. The pigment cells are shaped to form three cups, and within each cup are two to six photoreceptors, termed retinular cells (Kauri, 1962;Walley, 1969;Walker et til., 1987;Clare and Walker. 1989).…”
Section: Autoradiography Of Naiiplius Lar\-aementioning
confidence: 99%